Solar PV Project Implementation Feasibility Study based on Feed-in Tariff in Malaysia - Jali, Mohd Hafiz; SARKAWI, HAFEZ; Ahmad Izzuddin, Tarmizi; Sulaima, Mohamad Fani; Mohd Nasir, Mohamad Na'im (Research India Publications, 2014)
This paper illustrates the solar PV project implementation feasibility study based on Feed-in tariff embark by Malaysian government. The objectives of this study are to increase the awareness about the benefit of Feed-in Tariff (FiT) and to design a framework for solar PV project implementation in Malaysia. FIT is established to offer a guaranteed pricing structure for renewable energy production such as wind, solar, biogas and biogas. This could encourage greater investments in a renewable energy field in Malaysia. The framework is started by explaining the project lifecycle to set the milestone follow by explain the project Work Breakdown Structure (WBS) and Organization Breakdown Structure (OBS). Finally a proper project scheduling is established ensure a success project implementation.